Hábitos en hipertensión arterial y su relación con enfermedad cardiaca hipertensiva en el hospital Manuel Ygnacio Monteros - Armijos Guevara, Bolívar Stiward (2020)
terapéutica. Abstract Arterial Hypertension (AHT) is one of the most prevalent diseases worldwide and in the country. As it is a chronic disease, it has a high incidence of complications such as Hypertensive Heart Disease (HHD). This is mainly influenced by the patient's habits. It is therefore important to know, what habits in patients diagnosed with hypertension are related to the onset of hypertensive heart disease? The objectives were: To establish the prevalence of High Blood Pressure and Hypertensive Heart Disease by gender, to determine the most frequent habits in patients diagnosed with High Blood Pressure and to establish the strength of association between the habits present in patients diagnosed with HT, with the development of Hypertensive Heart Disease. The study was descriptive, correlational, cross- sectional, with a population of 100 patients who attended the Cardiology Area of the Manuel Ygnacio Monteros Hospital in the city of Loja. A 26-question survey was applied and data such as sex, age, and blood pressure, weight, and height values were collected from the most recent consultation. An HT prevalence of 159 patients was found; 91 female sex and 68 male sex; and with respect to ECH there was a prevalence of 25 patients, 15 female sex and 10 male sex. The most frequent habits were poor therapeutic adherence with 72%, sedentary lifestyle with 66% and overweight with 40%. The strength of association found was an OR 9.33 for sedentary lifestyle and an OR of 5.21 for poor therapeutic adherence. Key words: blood pressure, ventricular hypertrophy, sedentary lifestyle, therapeutic adherence.